2023
DOI: 10.1371/journal.pntd.0011016
|View full text |Cite
|
Sign up to set email alerts
|

Distinct features of the host-parasite interactions between nonadherent and adherent Trichomonas vaginalis isolates

Abstract: Cytoadherence of Trichomonas vaginalis to human vaginal epithelial cells (hVECs) was previously shown to involve surface lipoglycans and several reputed adhesins on the parasite. Herein, we report some new observations on the host-parasite interactions of adherent versus nonadherent T. vaginalis isolates to hVECs. The binding of the TH17 adherent isolate to hVECs exhibited an initial discrete phase followed by an aggregation phase inhibited by lactose. T. vaginalis infection immediately induced surface express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Recently, we found that actin cytoskeleton activity is involved in the morphogenesis and cytoadherence of T . vaginalis [ 27 , 28 ], prompting us to investigate the upstream signaling. T1 is a less adherent isolate with only the flagellate form freely swimming by flagellar motoring in suspension.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we found that actin cytoskeleton activity is involved in the morphogenesis and cytoadherence of T . vaginalis [ 27 , 28 ], prompting us to investigate the upstream signaling. T1 is a less adherent isolate with only the flagellate form freely swimming by flagellar motoring in suspension.…”
Section: Resultsmentioning
confidence: 99%
“…Flagellate-amoeboid transition is critical for T . vaginalis cytoadherence [ 27 , 28 ]. TH17 flagellate trophozoites were cultured on a glass slide to trigger contact-dependent amoeboid morphogenesis ( Fig 3A , S1 Movie ) and after 30 minutes, ~80% of the TH17 non-transfectant or HA- Tv PI4P5K transfectant trophozoites transformed into the amoeboid form but only ~40% of the K136A mutant transformed ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations